Characteristics, Availability, Demand, Challenges and Management of Present-Day Water Resources in Uganda - Francis N. W. Nsubuga; Edith N. Namutebi; Masoud Nsubuga-Ssenfuma (Research Advances in Environment, Geography and Earth Science Vol. 7, 2024)
The water resources of a country constitute one of its vital assets that significantly contribute to socio-economic development and poverty eradication. Surface and groundwater resources play a major role in domestic water supply, watering livestock, industrial operations, hydropower generation, agriculture, marine transport, fisheries, waste discharge, tourism, and environmental conservation. However, this resource is unevenly distributed in both time and space. The major source of water for these resources is direct rainfall, which has recently experienced variability that threatens the distribution of resources and water availability in Uganda. The annual rainfall received in Uganda varies from 500 mm to 2800 mm, with an average of 1180 mm received in two main seasons. The spatial distribution of rainfall has resulted in a network of great rivers and lakes that possess big potential for development. These resources are being developed and depleted at a fast rate, a situation that requires assessment to establish the present status of water resources in the country. The paper reviews the characteristics, availability, demand and importance of present-day water resources in Uganda as well as describe the various issues, challenges and management of water resources in the country. Evidence shows that in 2020, 83 percent of Ugandan households accessed either piped water or improved groundwater, compared to 61 percent in 2000. And the average water consumption per household per day also increased to 31.0 litres from 30.9 recorded in 2021.The major source of water for the country is the springs and wells. The new national strategy of bulk water supply is to meet rural settings demands including demands of water for livestock.